Halogen-free flame-retardant modified nylon 612 powder material for selective laser sintering and preparation method thereof

By preparing halogen-free flame-retardant modified nylon 612 powder material, the problems of insufficient flame retardancy and environmental protection of existing nylon 612 materials in the selective laser sintering process are solved, and nylon 612 powder material with high flame retardancy and high temperature resistance is realized, which is suitable for selective laser sintering technology.

CN119264472APending Publication Date: 2025-01-07湖南华曙新材料科技有限责任公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411223991.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing Nylon 612 materials suffer from insufficient flame retardancy, environmentally unfriendly processes, high costs, poor surface quality, and unstable performance during selective laser sintering, making it difficult to meet the demands of lightweight, green, and energy-saving trends.

Method used

A method for preparing halogen-free flame-retardant modified nylon 612 powder material was adopted. By reacting fiber micropowder with DOPO flame retardant in an aqueous solvent to form DDP salt, and then polymerizing it with nylon 612 salt solution, a nylon 612 powder material with high flame retardancy and high temperature resistance was prepared. Combining the characteristics of existing selective laser sintering technology, fiber micropowder was embedded to enhance the material performance.

Benefits of technology

The prepared halogen-free flame-retardant modified nylon 612 powder material has high flame retardancy and high temperature resistance, conforms to the green synthesis chemical route, reduces production costs, improves the thermal conductivity and surface quality of the material, and is suitable for selective laser sintering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264472A_ABST
    Figure CN119264472A_ABST
Patent Text Reader

Abstract

The invention discloses a halogen-free flame-retardant modified nylon 612 powder material for selective laser sintering and a preparation method of the halogen-free flame-retardant modified nylon 612 powder material. The preparation method comprises the following steps: (1) obtaining carboxylated fiber micro powder; (2) adding the DOPO salt solution into the decaethylenediamine aqueous solution, and uniformly mixing and stirring to obtain DDP salt; (3) adding dodecanedioic acid, hexanediamine and water into the reaction kettle to carry out neutralization reaction; (4) adding the carboxylated fiber micro powder, DDP salt, a molecular weight regulator and an antioxidant into the reaction kettle to carry out polymerization reaction; and 5, dissolving the halogen-free flame-retardant modified nylon 612 granules with an alcohol solvent, and sequentially carrying out spray granulation, drying, sieving and air grading treatment to prepare the halogen-free flame-retardant modified nylon 612 powder material for selective laser sintering. The preparation method is green, environmentally friendly, free of pollution, high in safety and low in production cost, and the prepared powder material has the advantages of being good in flame retardance, resistant to high temperature, controllable in performance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of additive manufacturing, and in particular to a halogen-free flame-retardant modified nylon 612 powder material for selective laser sintering and a preparation method thereof. Background Art

[0002] Nylon material is an engineering plastic with excellent performance. It has excellent mechanical properties, high modulus, acid and alkali resistance, abrasion resistance and other advantages. It has been widely used in aerospace, high-end automobiles, electronic daily necessities and other fields. As the above-mentioned application scenario industries develop towards lightweight, green environmental protection and energy saving, higher requirements are placed on the heat resistance and flame retardancy of polymer materials. Domestic and foreign companies have turned to the design and development of semi-aromatic high-temperature resistant nylon, which has the characteristics of strong designability, low cost, easy availability of raw materials, and easy regulation of product performance. It has become a research hotspot at home and abroad. However, my country has less research on high-temperature resistant and flame-retardant nylon, and key key materials still rely on imports.

[0003] Selective laser sintering is an additive manufacturing technology that uses laser as a power source to sinter powder materials. Its principle is based on the 3D data model of the workpiece. After the material powder is evenly spread through the powder spreading device, the laser scans to melt and bond it together until the workpiece is finally formed. Its essence is the local melting and adhesion of the powder and then cooling and solidification. This process is imperfect. The individual formed by sintering the spherical particles must have pores and other defects, and the surface quality is not high. Secondly, since the workpiece has a long residence time from heating and melting to cooling and solidification, the high molding temperature will cause the decomposition of the powder material, produce casting and corrosive gases, pollute the sintering equipment and environment, and also have an adverse effect on the surface quality and performance stability of the workpiece.

[0004] At present, alcohol is used as solvent in the synthesis of nylon 612, which has high industrial cost, explosive and flammable solvents that pollute the environment, do not meet the environmental protection requirements of the process, and the material is not flame retardant. In order to reduce costs and improve the flame retardancy of materials, it is designed to use water as a solvent to synthesize a halogen-free flame retardant modified nylon 612 material. This is the current development trend of green synthetic chemistry, pollution-free, low safety and cost-reducing process.

[0005] Therefore, how to prepare a nylon 612 powder material with good flame retardancy, high temperature resistance, environmentally friendly process, controllable performance and suitable for selective laser sintering needs to be solved urgently. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a halogen-free flame retardant modified nylon 612 powder material for selective laser sintering and a preparation method thereof. The preparation method of the present invention is green, environmentally friendly and pollution-free, has high safety, low production cost, and no solvent residue. The product does not require post-treatment and conforms to the green synthetic chemical route. Moreover, the halogen-free flame retardant modified nylon 612 powder material prepared by the present invention has the advantages of good flame retardancy, high temperature resistance, controllable performance, etc.

[0007] To achieve the above object, the present invention provides a method for preparing a halogen-free flame-retardant modified nylon 612 powder material for selective laser sintering, comprising the following steps:

[0008] Step (1): adding fiber powder to concentrated nitric acid solution, and ultrasonically vibrating at 60-80° C. for 4-6 hours, then diluting, filtering and washing to pH=7.0, and then vacuum drying at 50-60° C. to constant weight to obtain dried fiber powder; adding the dried fiber powder to a mixed solution of silane coupling agent and thionyl chloride, and ultrasonically vibrating at 70-80° C. for 8-10 hours, then washing, filtering, and vacuum drying at 50-60° C., and grinding for standby use to obtain carboxylated fiber powder;

[0009] Step (2): mixing decaethylenediamine and deionized water and heating and stirring to dissolve to obtain a decaethylenediamine aqueous solution; mixing and dissolving DOPO flame retardant powder and adipic acid solution to obtain a DOPO salt solution, and then adding the DOPO salt solution to the decaethylenediamine aqueous solution and stirring to obtain a DOPO salt solution; reacting for 1 to 2 hours until the solution turns light yellow, cooling the solution to room temperature, filtering, and washing to obtain a DDP salt;

[0010] Step (3): adding dodecanedioic acid, hexamethylenediamine, DDP salt and water into a reaction kettle for neutralization reaction to obtain a nylon 612 salt solution, and testing the pH value of the nylon 612 salt solution to be 7.0-8.0;

[0011] Step (4): adding carboxylated fiber powder, molecular weight regulator and antioxidant into a reactor, and polymerizing with the nylon 612 salt solution in the reactor, followed by discharging, cooling, pelletizing and drying to obtain halogen-free flame-retardant modified nylon 612 pellets;

[0012] Step (5): dissolving the halogen-free flame-retardant modified nylon 612 pellets in an alcohol solvent, and then sequentially subjecting the pellets to spray granulation, drying, screening and air classification to obtain a halogen-free flame-retardant modified nylon 612 powder material for selective laser sintering having an average particle size of 50 μm to 80 μm.

[0013] Preferably, in step (1), the ratio of the mass of the fiber powder to the volume of the concentrated nitric acid solution is 1 g:60 ml.

[0014] Preferably, in step (1), the ratio of the mass of the dried fiber powder, the volume of thionyl chloride and the volume of the silane coupling agent is 0.5 g:40 ml:1 ml.

[0015] Preferably, the mass fraction of the silane coupling agent in the mixed solution is 2% to 5%.

[0016] Preferably, the power of the ultrasonic oscillation at 70-80° C. in step (1) is 200-250 W.

[0017] Preferably, the concentrated nitric acid solution is nitric acid with a concentration of 69.7%.

[0018] Preferably, the fiber powder is one of carbon fiber, glass fiber, aramid fiber and carbon nanotube.

[0019] Preferably, in step (2), the mass ratio of DOPO flame retardant powder to adipic acid solution is 1:1-2.

[0020] Preferably, in step (2), the mass ratio of decaethylenediamine to deionized water is 1:2-3.

[0021] Preferably, in step (2), decaethylenediamine and deionized water are heated to 50-70° C. and stirred to dissolve.

[0022] Preferably, in step (3), the molar mass ratio of dodecanedioic acid to hexamethylenediamine is 1 to 1.05:1.

[0023] Preferably, in step (3), the ratio of the sum of the masses of dodecanedioic acid and hexamethylenediamine to the mass of deionized water is 1:1 to 1.25.

[0024] Preferably, the water in step (3) is one or more of deionized water and industrial water.

[0025] Preferably, when the neutralization reaction occurs in step (3), uniform mixing is performed at a stirring rate of 120 to 180 r / min, the reaction temperature is 90 to 110° C., and the reaction time is 2 to 4 h.

[0026] Preferably, in step (4), the amount of the molecular weight regulator added is 0.1% to 0.3% of the mass of the nylon 612 salt solution, the amount of the antioxidant added is 0.01% to 0.02% of the mass of the nylon 612 salt solution, and the amount of the DDP salt added is 5% to 15% of the mass of the nylon 612 salt solution.

[0027] Preferably, the process of the polymerization reaction in step (4) is as follows: the temperature in the reactor is raised and the exhaust is first vented for 5 to 10 minutes; then the exhaust valve is closed and the temperature is raised to 120 to 140° C., and then the water vapor is discharged for 20 to 50 minutes, and the pressure is maintained at normal pressure; then the exhaust valve is closed and the temperature is raised to 230 to 260° C., and the pressure is 1.0 to 1.5 MPa; then the polymerization reaction is carried out at a pressure of 1.0 to 1.5 MPa for 2 to 6 hours; finally, the pressure is reduced to normal pressure at a pressure reduction rate of 0.1 to 0.16 MPa / 10 min and the material is discharged. The pressure reduction time is 90 to 140 minutes, and the temperature in the reactor is 230 to 260° C. when the material is discharged.

[0028] Preferably, the halogen-free flame retardant modified nylon 612 pellets obtained in step (4) have a relative viscosity of 1.9 to 2.8 when tested by a 25° C. sulfuric acid method.

[0029] Preferably, the alcohol solvent in step (5) is one of methanol, ethanol and propanol.

[0030] Preferably, in step (5), a 60-120 mesh sieve is used for sieving.

[0031] Preferably, the silane coupling agent is one or more of trimethoxysilane, vinyltrimethoxysilane, 3-aminopropyltriethoxysilane, and N-(2-aminoethyl)-3-aminopropyltrimethoxysilane.

[0032] Preferably, the antioxidant is one or more of antioxidant 300, antioxidant 1010, antioxidant 168, and antioxidant 1098.

[0033] Preferably, the molecular weight regulator is one or more of terephthalic acid, glacial acetic acid, dodecanedioic acid, adipic acid, and sebacic acid.

[0034] A halogen-free flame-retardant modified nylon 612 powder material for selective laser sintering is prepared by adopting the preparation method of the halogen-free flame-retardant modified nylon 612 powder material.

[0035] The beneficial effects of the present invention are:

[0036] (1) The halogen-free flame-retardant modified nylon 612 powder material for laser sintering in the present invention is prepared by modifying the DOPO flame retardant into DDP salt and reacting with hexamethylenediamine monomer to form a flame-retardant nylon 6 monomer; the polymerized nylon 612 molecular chain structure branch chains have flame-retardant functional groups, which enables the nylon 612 material to have excellent expansion flame-retardant effect. At the same time, the addition of fiber powder enhances the strength of the residual carbon of the nylon 612 substrate and increases the material's ability to isolate oxygen and transfer heat. The prepared modified nylon 612 powder material has high flame retardancy and high temperature resistance.

[0037] (2) The present invention uses nylon salt and polymerization in one step to prepare halogen-free flame-retardant modified nylon 612 powder material. The salt preparation and polymerization process are simple and have strong applicability. The halogen-free flame retardant and water are used as solvents, which are green and environmentally friendly, highly safe, and have low production costs. The product does not require post-treatment and is in line with the green synthetic chemical route. It has great academic value and application scenarios, and is more practical for industrial production.

[0038] (3) At the same time, the present invention combines the characteristics of existing selective laser 3D printing technology, and embeds fiber micropowder into the nylon matrix, thereby improving the internal thermal conductivity, heat distribution and heat-bearing capacity of the material, and reducing the thermal stress caused by high-energy laser rapid melting and rapid cooling. The treated fiber micropowder is tightly bonded to the nylon 612 resin matrix, and the interface effect is good, giving full play to the effect of fiber micropowder material in reinforcing polymer materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0040] Figure 1 It is the carboxylation structure of the fiber micropowder of the present invention.

[0041] Figure 2 This is the DDP salt reaction process of the present invention.

[0042] Figure 3 This is the reaction process of the DDP-PA6 monomer structure of the present invention.

[0043] Figure 4 This is the reaction process of the DDP-PA612 monomer structure of the present invention.

[0044] Figure 5 This is an electron microscope image of the halogen-free flame-retardant modified nylon 612 powder of the present invention. DETAILED DESCRIPTION

[0045] Examples are given below to further illustrate the present invention.

[0046] In addition, it is worth noting that: 1. The intrinsic viscosity [η] of the halogen-free flame-retardant and high-temperature resistant PA612 pellets obtained in the following examples is prepared with concentrated sulfuric acid as solvent to a solution with a concentration of 0.5 g / dL, and tested with an Ubbelohde viscometer at 25°C; 2. The limiting oxygen index of the halogen-free flame-retardant and high-temperature resistant PA612 pellets obtained in the following examples is obtained by making them into 120×6.5×3 mm 3The vertical burning grade of the halogen-free flame-retardant and high-temperature resistant PA612 powder obtained in the following examples is obtained by making it into a 125×12.7×3mm 3 4. The tensile strength of the halogen-free flame retardant and high temperature resistant PA612 powder obtained in the following examples is measured by making it into dumbbell-shaped specimens with a narrow neck width of 4.0±0.1mm and a thickness of 2.0±0.1mm, and using an INSTRON3366 universal testing machine according to ASTMD-638 standard.

[0047] Comparative Example 1

[0048] 1. Weigh 23.2kg of dodecanedioic acid, 11.7kg of hexamethylenediamine, 0.015kg of antioxidant 168, 0.18kg of terephthalic acid and 40kg of water, add them into the reactor, heat up and exhaust for 8 minutes, then close the exhaust valve; stir at a stirring rate of 170r / min, heat to 105℃, react for 4h to obtain PA612 salt solution, and measure the pH value of the PA612 salt solution to be 7.5, set aside. Continue to raise the temperature in the reactor to 120°C, open the exhaust valve, drain the water vapor for 50 minutes, and maintain the pressure at normal pressure; then close the exhaust valve and raise the temperature to 240°C and the pressure to 1.5MPa; then polymerize at a pressure of 1.5MPa for 2h; finally, reduce the pressure to normal pressure at a decompression rate of 0.16MPa / 10min and then discharge the material. The decompression time is 140min. The temperature in the reactor is 230°C when discharging the material. After cooling, pelletizing and drying, nylon 612 material pellets are obtained.

[0049] 2. The nylon 612 pellets were dissolved in ethanol and sprayed into a granulation tower in the form of droplets for spray granulation to obtain wet granular powder with an average particle size of 63 μm. The wet granular powder was then dried, sieved with a 100-mesh sieve and air-classified to obtain nylon 612 powder material with an average particle size of 57 μm.

[0050] The nylon 612 powder has an intrinsic viscosity [η] of 1.92 dL / g, a limiting oxygen index of 21.4%, a vertical combustion grade of V-2, and a tensile strength of 42 MPa.

[0051] Comparative Example 2

[0052] 1. Dissolve 4.5 kg of DOPO flame retardant powder in 5 kg of adipic acid solution and stir evenly to obtain DOPO salt solution; heat 600 g of deionized water and 1.5 kg of deionized water to 60 ° C and dissolve and stir to obtain deionized water solution; then add the DOPO salt solution to the deionized water solution and stir evenly. After reacting for 1 hour, when the solution turns light yellow, cool the solution to room temperature, wash and filter to obtain 3.7 kg of DDP salt.

[0053] 2. Weigh 23.8 kg of dodecanedioic acid, 12 kg of hexamethylenediamine and 43 kg of water into a reactor for neutralization reaction, and mix and stir evenly at a stirring rate of 150 r / min. The temperature in the reactor is 100°C, and the reaction time is 4 hours to obtain a PA612 salt solution. The pH value of the PA612 salt solution is measured to be 7.2 and is set aside.

[0054] 3. Add 4kg DDP salt, 0.012kg antioxidant 1010 and 0.18kg terephthalic acid into the reactor and react with the nylon 612 salt solution in the reactor. The polymerization process is as follows: heat the reactor and exhaust for 6 minutes; then close the exhaust valve and heat to 120°C, then open the exhaust valve and drain steam for 50 minutes, and keep the pressure at normal pressure; then close the exhaust valve and heat to 250°C, the pressure is 1.5MPa; then polymerize for 2 hours at a pressure of 1.5MPa; refer to the monomer structure of DDP-PA6 and DDP-PA612 for details. Figure 3 and Figure 4 Finally, the pressure was reduced to normal pressure at a rate of 0.12MPa / 10min and the material was discharged. The pressure reduction time was 110min. The temperature in the reactor was 250℃ when the material was discharged. After cooling, pelletizing and drying, halogen-free flame-retardant modified nylon 612 pellets were obtained.

[0055] 4. The halogen-free flame retardant modified nylon 612 pellets were dissolved in ethanol and sprayed into a granulation tower in the form of droplets for spray granulation to obtain wet granular powder with an average particle size of 78 μm. The wet granular powder was then dried, sieved through an 80-mesh sieve and air-classified to obtain a halogen-free flame retardant modified nylon 612 powder material for selective laser sintering with an average particle size of 64 μm.

[0056] The halogen-free flame-retardant modified nylon 612 powder has an intrinsic viscosity [η] of 1.97 dL / g, a limiting oxygen index of 26.1%, a vertical combustion grade of V-1, and a tensile strength of 37 MPa.

[0057] Example 1

[0058] 1. Add 5.5 kg of carbon fiber powder to concentrated nitric acid solution, and ultrasonically vibrate at 60 ° C for 6 hours, then dilute, filter and wash to pH = 7.0, and then vacuum dry at 50 ° C to constant weight to obtain dried carbon fiber powder; add the dried carbon fiber powder to a mixed solution of trimethoxysilane and thionyl chloride with a trimethoxysilane mass fraction of 3%, and ultrasonically vibrate at 80 ° C with 250W for 10 hours, then wash, filter, and vacuum dry at 60 ° C, and grind for standby use to obtain 5 kg of carboxylated carbon fiber powder for standby use. The carboxylation structure of the fiber powder can be found in Figure 1 shown.

[0059] 2. Dissolve 6 kg of DOPO flame retardant powder in 7 kg of adipic acid solution and stir evenly to obtain a DOPO salt solution; heat 800 g of decaethylenediamine and 2 kg of deionized water to 60 ° C and dissolve and stir to obtain a decaethylenediamine aqueous solution; add the DOPO salt solution to the decaethylenediamine aqueous solution and stir evenly. After reacting for 2 hours, the solution turns light yellow to generate a DDP salt solution. The solution is cooled to room temperature, washed, filtered, dried, and ground to obtain 5.4 kg of DDP salt for standby use. The DDP salt reaction process is shown in Figure 2 shown.

[0060] 3. Weigh 23.3 kg of dodecanedioic acid, 11.8 kg of hexamethylenediamine and 42 kg of water, add them into the reactor, heat and dissolve them to cause neutralization reaction, stir at a stirring rate of 180 r / min, the reaction temperature is 90 ° C, the reaction time is 3 h, and nylon 612 salt solution is obtained. The pH value of the nylon 612 salt solution is tested to be 7.5.

[0061] 4. Add 5kg of carboxylated carbon fiber powder, 5.4kg of DDP salt, 0.01kg of antioxidant 1010 and 0.15kg of adipic acid into the reactor, stir evenly, and react with the nylon 612 salt solution in the reactor. The polymerization process is as follows: heat the reactor and exhaust for 10 minutes; then close the exhaust valve and heat to 140°C, then open the exhaust valve and drain steam for 30 minutes, and keep the pressure at normal pressure; then close the exhaust valve and heat to 240°C, the pressure is 1.5MPa; then polymerize at a pressure of 1.5MPa for 6 hours; DDP-PA6 and DDP-PA612 monomer structures refer to Figure 3 and Figure 4 Finally, the pressure was reduced to normal pressure at a rate of 0.16MPa / 10min and the material was discharged. The pressure reduction time was 90min. The temperature in the reactor was 245°C when the material was discharged. After cooling, pelletizing and drying, halogen-free flame-retardant modified nylon 612 pellets were obtained.

[0062] 5. Dissolve the halogen-free flame retardant modified nylon 612 pellets in ethanol and spray them into a granulation tower in the form of droplets for spray granulation to obtain wet granular powder with an average particle size of 89 μm. Then, the wet granular powder is dried, sieved through a 60-mesh screen and air-classified in turn to obtain halogen-free flame retardant modified nylon 612 powder material for selective laser sintering with an average particle size of 78 μm. Figure 5 Electron micrograph shown.

[0063] The halogen-free flame-retardant modified nylon 612 powder has an intrinsic viscosity [η] of 2.45 dL / g, a limiting oxygen index of 27.4%, a vertical combustion grade of V-0, no melting drop, and a tensile strength of 47 MPa.

[0064] Example 2

[0065] 1. Add 4.5 kg of carbon nanotube powder to concentrated nitric acid solution, and ultrasonically vibrate at 60° C. for 6 h, then dilute, filter and wash to pH=7.0, and then vacuum dry at 60° C. to constant weight to obtain dry carbon nanotube powder; add the dry carbon nanotube powder to a mixed solution of trimethoxysilane and thionyl chloride with a trimethoxysilane mass fraction of 3%, and ultrasonically vibrate at 80° C. at 250 W for 8 h, then wash, filter, and vacuum dry at 60° C., and grind for standby use to obtain 4 kg of carboxylated carbon fiber powder for standby use. The carboxylation structure of the fiber powder can be found in Figure 1 shown.

[0066] 2. Dissolve 7kg of DOPO flame retardant powder in 8kg of adipic acid solution and stir evenly to obtain DOPO salt solution; heat 700g of decaethylenediamine and 1.6kg of deionized water to 60°C and dissolve and stir to obtain decaethylenediamine aqueous solution; add DOPO salt solution to decaethylenediamine aqueous solution and stir evenly. After reacting for 2h, when the solution turns light yellow, DDP salt solution is generated. Cool the solution to room temperature, wash, filter, dry, and grind to obtain 6.8kg of DDP salt for standby use. For the DDP salt reaction process, refer to Figure 2 shown.

[0067] 3. Weigh 21.85 kg of dodecanedioic acid, 11.2 kg of hexamethylenediamine and 39 kg of water, add them into the reactor, heat and dissolve them to cause neutralization reaction, stir at a stirring rate of 150 r / min, the reaction temperature is 110°C, the reaction time is 3 h, and nylon 612 salt solution is obtained. The pH value of the nylon 612 salt solution is tested to be 7.4.

[0068] 4. Add 4kg of carboxylated carbon nanotube powder, 6.8kg of DDP salt, 0.012kg of antioxidant 168 and 0.16kg of terephthalic acid into the reactor, stir evenly, and react with the nylon 612 salt solution in the reactor to polymerize. The polymerization process is as follows: heat the reactor and exhaust for 5 minutes; then close the exhaust valve and heat to 130°C, then open the exhaust valve and drain steam for 45 minutes, and keep the pressure at normal pressure; then close the exhaust valve and heat to 260°C, the pressure is 1.2MPa; then polymerize for 5 hours at a pressure of 1.2MPa; DDP-PA6 and DDP-PA612 monomer structures refer to Figure 3 and Figure 4 Finally, the pressure was reduced to normal pressure at a rate of 0.1 MPa / 10 min and the material was discharged. The pressure reduction time was 140 min. The temperature in the reactor was 260°C when the material was discharged. After cooling, pelletizing and drying, halogen-free flame-retardant modified nylon 612 pellets were obtained.

[0069] 5. Dissolve the halogen-free flame retardant modified nylon 612 pellets in ethanol and spray them into a granulation tower in the form of droplets for spray granulation to obtain wet granular powder with an average particle size of 72μm. Then, the wet granular powder is dried, sieved through a 100-mesh sieve, and air-classified to obtain a halogen-free flame retardant modified nylon 612 powder material for selective laser sintering with an average particle size of 67um. Figure 5 Electron micrograph shown.

[0070] The halogen-free flame-retardant modified nylon 612 powder has an intrinsic viscosity [η] of 2.51 dL / g, a limiting oxygen index of 29.4%, a vertical combustion grade of V-0, no melting drop, and a tensile strength of 55 MPa.

[0071] Example 3

[0072] 1. Add 6.5 kg of carbon fiber powder to concentrated nitric acid solution, and ultrasonically vibrate at 60 ° C for 6 hours, then dilute, filter and wash to pH = 7.0, and then vacuum dry at 50 ° C to constant weight to obtain dried carbon fiber powder; add the dried carbon fiber powder to a mixed solution of vinyl trimethoxy silane and thionyl chloride with a mass fraction of 3% of vinyl trimethoxy silane, and ultrasonically vibrate at 80 ° C with 250W for 10 hours, then wash, filter, and vacuum dry at 60 ° C, and grind for standby use to obtain 6 kg of carboxylated carbon fiber powder for standby use. The carboxylation structure of the fiber powder can be found in Figure 1 shown.

[0073] 2. Dissolve 10 kg of DOPO flame retardant powder in 11 kg of adipic acid solution and stir evenly to obtain a DOPO salt solution; heat 920 g of decaethylenediamine and 1.9 kg of deionized water to 60 ° C and dissolve and stir to obtain a decaethylenediamine aqueous solution; add the DOPO salt solution to the decaethylenediamine aqueous solution and stir evenly. After reacting for 2 hours, the solution turns light yellow to generate a DDP salt solution. The solution is cooled to room temperature, washed, filtered, dried, and ground to obtain 9 kg of DDP salt for standby use. The DDP salt reaction process is shown in Figure 2 shown.

[0074] 3. Weigh 20.8 kg of dodecanedioic acid, 10.7 kg of hexamethylenediamine and 35 kg of water, add them into the reactor, heat and dissolve them to cause neutralization reaction, stir at a stirring rate of 180 r / min, the reaction temperature is 100 ° C, the reaction time is 3 h, and nylon 612 salt solution is obtained. The pH value of the nylon 612 salt solution is tested to be 7.4.

[0075] 4. Add 6kg of carboxylated carbon fiber powder, 9kg of DDP salt, 0.01kg of antioxidant 1010 and 0.15kg of terephthalic acid into the reactor, stir evenly, and react with the nylon 612 salt solution in the reactor. The polymerization process is as follows: the reactor is heated and vented for 8 minutes; then the exhaust valve is closed and the temperature is raised to 140°C, and then the exhaust valve is opened to drain steam for 30 minutes, and the pressure is kept at normal pressure; then the exhaust valve is closed and the temperature is raised to 230°C, and the pressure is 1.0MPa; then the polymerization reaction is carried out at a pressure of 1.0MPa for 6 hours; the monomer structures of DDP-PA6 and DDP-PA612 refer to Figure 3 and Figure 4 Finally, the pressure was reduced to normal pressure at a rate of 0.14 MPa / 10 min and the material was discharged. The pressure reduction time was 100 min. The temperature in the reactor was 230°C during the discharge. After cooling, pelletizing and drying, halogen-free flame-retardant modified nylon 612 pellets were obtained.

[0076] 5. Dissolve the halogen-free flame retardant modified nylon 612 pellets in methanol and spray them into a granulation tower in the form of droplets for spray granulation to obtain wet granular powder with an average particle size of 76μm. The wet granular powder is then dried, sieved through a 120-mesh screen and air-classified to obtain a halogen-free flame retardant modified nylon 612 powder material for selective laser sintering with an average particle size of 64um. Figure 5 Electron micrograph shown.

[0077] The halogen-free flame-retardant modified nylon 612 powder has an intrinsic viscosity [η] of 1.93 dL / g, a limiting oxygen index of 28.3%, a vertical combustion grade of V-0, no melting drop, and a tensile strength of 42 MPa.

[0078] Example 4

[0079] 1. Add 9 kg of glass fiber powder to concentrated nitric acid solution, and ultrasonically vibrate at 60°C for 6 hours, then dilute, filter and wash to pH = 7.0, and then vacuum dry at 60°C to constant weight to obtain dried glass fiber powder; add dried carbon fiber powder to a mixed solution of vinyl trimethoxy silane and thionyl chloride with a mass fraction of 2% vinyl trimethoxy silane, and ultrasonically vibrate at 70°C at 250W for 8 hours, then wash, filter, and vacuum dry at 60°C, and grind for standby use to obtain 8 kg of carboxylated glass fiber powder for standby use. The carboxylation structure of the fiber powder can be found in Figure 1 shown.

[0080] 2. Dissolve 5 kg of DOPO flame retardant powder in 5.8 kg of adipic acid solution and stir evenly to obtain a DOPO salt solution; heat 700 g of decaethylenediamine and 1.7 kg of deionized water to 70 ° C and dissolve and stir to obtain a decaethylenediamine aqueous solution; add the DOPO salt solution to the decaethylenediamine aqueous solution and stir evenly. After reacting for 2 hours, the solution turns light yellow to generate a DDP salt solution. The solution is cooled to room temperature, washed, filtered, dried, and ground to obtain 4.8 kg of DDP salt for standby use. The DDP salt reaction process is shown in Figure 2 shown.

[0081] 3. Weigh 23.4 kg of dodecanedioic acid, 11.9 kg of hexamethylenediamine and 42 kg of water, add them into the reactor, heat and dissolve them to cause neutralization reaction, stir at a stirring rate of 120 r / min, the reaction temperature is 110°C, the reaction time is 2 h, and nylon 612 salt solution is obtained. The pH value of the nylon 612 salt solution is tested to be 7.1.

[0082] 4. Add 8kg of carboxylated glass fiber powder, 4.8kg of DDP salt, 0.015kg of antioxidant 1010 and 0.2kg of glacial acetic acid into the reactor, stir evenly, and react with the PA612 salt solution in the reactor. The polymerization process is as follows: the reactor is heated and vented for 10 minutes; then the exhaust valve is closed and the temperature is raised to 130°C, and then the exhaust valve is opened to drain steam for 45 minutes, and the pressure is maintained at normal pressure; then the exhaust valve is closed and the temperature is raised to 250°C, and the pressure is 1.2MPa; then the polymerization reaction is carried out at a pressure of 1.2MPa for 6 hours; the monomer structures of DDP-PA6 and DDP-PA612 refer to Figure 3 and Figure 4 Finally, the pressure was reduced to normal pressure at a rate of 0.14 MPa / 10 min and the material was discharged. The pressure reduction time was 120 min. The temperature in the reactor was 250°C during the discharge. After cooling, pelletizing and drying, halogen-free flame-retardant modified nylon 612 pellets were obtained.

[0083] 5. Dissolve the halogen-free flame retardant modified nylon 612 pellets in ethanol and spray them into a granulation tower in the form of droplets for spray granulation to obtain wet granular powder with an average particle size of 73μm. Then, the wet granular powder is dried, sieved through a 120-mesh screen and air-classified in turn to obtain halogen-free flame retardant modified nylon 612 powder material for selective laser sintering with an average particle size of 61um. See Figure 5 Electron micrograph shown.

[0084] The halogen-free flame-retardant modified nylon 612 powder has an intrinsic viscosity [η] of 2.01 dL / g, a limiting oxygen index of 27.4%, a vertical combustion grade of V-1, no melting drop, and a tensile strength of 40 MPa.

[0085] The following table is a comparison table of the performance parameters of nylon 612 powder prepared in Comparative Examples 1 and 2 and Examples 1-4:

[0086]

[0087] As can be seen from the table, in Comparative Example 1, the nylon 612 powder without flame retardant and fiber powder has the smallest oxygen index and poor flame retardant performance; while the nylon 612 powder in other embodiments has a high oxygen index and a flame retardant level of V1-V0, but in Comparative Example 2, no fiber powder is added, and its performance is poor relying solely on flame retardant filling, and the flame retardant effect is not obvious. In Example 4, the addition of glass fiber powder does not have a significant flame retardant effect of carbon fiber and carbon nanotubes.

[0088] The above description of the disclosed embodiments is intended only to enable those skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a halogen-free flame-retardant modified nylon 612 powder material for selective laser sintering, comprising the following steps: Step (1): adding fiber powder to concentrated nitric acid solution, and ultrasonically vibrating at 60-80° C. for 4-6 hours, then diluting, filtering and washing to pH=7.0, and then vacuum drying at 50-60° C. to constant weight to obtain dried fiber powder; adding the dried fiber powder to a mixed solution of silane coupling agent and thionyl chloride, and ultrasonically vibrating at 70-80° C. for 8-10 hours, then washing, filtering, and vacuum drying at 50-60° C., and grinding for standby use to obtain carboxylated fiber powder; Step (2): mixing decaethylenediamine and deionized water and heating and stirring to dissolve to obtain a decaethylenediamine aqueous solution; mixing and dissolving DOPO flame retardant powder and adipic acid solution to obtain a DOPO salt solution, and then adding the DOPO salt solution to the decaethylenediamine aqueous solution and stirring to obtain a DOPO salt solution; reacting for 1 to 2 hours until the solution turns light yellow, cooling the solution to room temperature, filtering, and washing to obtain a DDP salt; Step (3): adding dodecanedioic acid, hexamethylenediamine and water into a reaction kettle for neutralization reaction to obtain a nylon 612 salt solution, and testing the pH value of the nylon 612 salt solution to be 7.0-8.0; Step (4): adding carboxylated fiber powder, DDP salt, molecular weight regulator and antioxidant into a reactor, and polymerizing with the nylon 612 salt solution in the reactor, followed by discharging, cooling, pelletizing and drying to obtain halogen-free flame-retardant modified nylon 612 pellets; Step (5): dissolving the halogen-free flame-retardant modified nylon 612 pellets in an alcohol solvent, and then sequentially subjecting the pellets to spray granulation, drying, screening and air classification to obtain a halogen-free flame-retardant modified nylon 612 powder material for selective laser sintering having an average particle size of 50 μm to 80 μm.

2. The method for preparing the halogen-free flame-retardant modified nylon 612 powder material for selective laser sintering according to claim 1, characterized in that: The ratio of the mass of the fiber powder to the volume of the concentrated nitric acid solution in step (1) is 1 g:60 ml; the ratio of the mass of the dried fiber powder, the volume of thionyl chloride and the volume of the silane coupling agent in step (1) is 0.5 g:40 ml:1 ml; The mass fraction of the silane coupling agent in the mixed solution is 2% to 5%; the power of the ultrasonic oscillation at 70 to 80° C. in step (1) is 200 to 250 W.

3. The method for preparing the halogen-free flame-retardant modified nylon 612 powder material for selective laser sintering according to claim 1, characterized in that: The concentrated nitric acid solution is nitric acid with a concentration of 69.7%; the fiber powder is one of carbon fiber, glass fiber, aramid fiber and carbon nanotube.

4. The method for preparing the halogen-free flame-retardant modified nylon 612 powder material for selective laser sintering according to claim 1, characterized in that: In step (2), the mass ratio of DOPO flame retardant powder to adipic acid solution is 1:1-2; in step (2), the mass ratio of decaethylenediamine to deionized water is 1:2-3; in step (2), decaethylenediamine and deionized water are heated to 50-70° C. and stirred to dissolve.

5. The method for preparing the halogen-free flame-retardant modified nylon 612 powder material for selective laser sintering according to claim 1, characterized in that: The molar mass ratio of dodecanedioic acid to hexamethylenediamine in step (3) is 1-1.05:1; the mass ratio of the sum of the mass of dodecanedioic acid and hexamethylenediamine to the mass of water in step (3) is 1:1-1.25; the water in step (3) is one or more of deionized water and industrial water; when the neutralization reaction occurs in step (3), the mixture is uniformly mixed at a stirring rate of 120-180 r / min, the reaction temperature is 90-110° C., and the reaction time is 2-4 h.

6. The method for preparing the halogen-free flame-retardant modified nylon 612 powder material for selective laser sintering according to claim 1, characterized in that: In step (4), the amount of the molecular weight regulator added is 0.1% to 0.3% of the mass of the nylon 612 salt solution, the amount of the antioxidant added is 0.01% to 0.02% of the mass of the nylon 612 salt solution, and the amount of the DDP salt added is 5% to 15% of the mass of the nylon 612 salt solution.

7. The method for preparing the halogen-free flame-retardant modified nylon 612 powder material for selective laser sintering according to claim 1, characterized in that: The process of the polymerization reaction in step (4) is as follows: the temperature in the reactor is raised and the exhaust is first performed for 5 to 10 minutes; then the exhaust valve is closed and the temperature is raised to 120 to 140° C., and then the water vapor is discharged for 20 to 50 minutes, and the pressure is maintained at normal pressure; then the exhaust valve is closed and the temperature is raised to 230 to 260° C., and the pressure is 1.0 to 1.5 MPa; then the polymerization reaction is carried out at a pressure of 1.0 to 1.5 MPa for 2 to 6 hours; finally, the pressure is reduced to normal pressure at a pressure reduction rate of 0.1 to 0.16 MPa / 10 min and the material is discharged. The pressure reduction time is 90 to 140 minutes, and the temperature in the reactor is 230 to 260° C. when the material is discharged.

8. The method for preparing the halogen-free flame-retardant modified nylon 612 powder material for selective laser sintering according to claim 1, characterized in that: The halogen-free flame-retardant modified nylon 612 pellets obtained in step (4) have a relative viscosity of 1.9 to 2.8 when tested by a 25° C. sulfuric acid method.

9. The method for preparing the halogen-free flame-retardant modified nylon 612 powder material for selective laser sintering according to claim 1, characterized in that: The silane coupling agent is one or more of trimethoxysilane, vinyl trimethoxysilane, 3-aminopropyl triethoxysilane, and N-(2-aminoethyl)-3-aminopropyl trimethoxysilane; the antioxidant is one or more of antioxidant 300, antioxidant 1010, antioxidant 168, and antioxidant 1098; the molecular weight regulator is one or more of terephthalic acid, glacial acetic acid, dodecanedioic acid, adipic acid, and sebacic acid; The alcohol solvent in step (5) is one of methanol, ethanol and propanol; and a 60-120 mesh sieve is used for sieving in step (5).

10. A halogen-free flame-retardant modified nylon 612 powder material for selective laser sintering, characterized in that: The halogen-free flame-retardant modified nylon 612 powder material is prepared by the preparation method of any one of claims 1 to 9.